Positive Crosstalk Between Hedgehog and NF-κB Pathways Is Dependent on KRAS Mutation in Pancreatic Ductal Adenocarcinoma - Wang, Yuqiong; Wang, Dan; Dai, Yanmiao; Kong, Xiangyu; Zhu, Xian; Fan, Yunxia; Wang, Yaodong; Wu, Hongyu; Jin, Jing; Yao, Wenzhu; Gao, Jun; Wang, Kaixuan; et al. (Frontiers in Oncology, 2021)
It has been shown that aberrant activation of the Hedgehog (Hh) and nuclear factor-kappa B (NF-κB) signaling pathways plays an important role in the pancreatic carcinogenesis, and KRAS mutation is a hallmark of pancreatic ductal adenocarcinoma (PDAC). Until now, the role of KRAS mutation in the context of crosstalk between Hh and NF-κB signaling pathways in PDAC has not been investigated. This study was to determine whether the crosstalk between the Hh and NF-κB pathways is dependent on KRAS mutation in PDAC. The correlation between Gli1, Shh, NF-κB p65 expression and KRAS mutation in PDAC tissues was firstly examined by immunohistochemistry. Next, Western blotting, qPCR, and immunofluorescence were conducted to examine the biological effects of interleukin-1β (IL-1β) and tumor necrosis factor-alpha (TNF-α) as NF-κB signaling agonists, Shh as an Hh ligand alone or in combination with KRAS small interfering RNA (si-KRAS) in KRAS-mutant PDAC cells (MT-KRAS; SW1990 and Panc-1), wild-type KRAS PDAC cells (WT-KRAS; BxPC-3) and mutant KRAS knock-in BxPC-3 cells in vitro as well as tumor growth in vivo. KRAS mutation-dependent crosstalk between Hh and NF-κB in PDAC cells was further assessed by Ras activity and luciferase reporter assays. The aberrant Hh and NF-κB pathway activation was found in PDAC tissues with KRAS mutation. The same findings were confirmed in MT-KRAS PDAC cells and MT-KRAS knock-in BxPC-3 cells, whereas this activation was not observed in WT-KRAS PDAC cells. However, the activation was significantly down-regulated by KRAS silencing in MT-KRAS PDAC cells. Furthermore, MT-KRAS cancer cell proliferation and survival in vitro and tumor growth after inoculation with MT-KRAS cells in vivo were promoted by NF-κB and Hh signaling activation. The pivotal factor for co-activation of NF-κB and Hh signaling is MT-KRAS protein upregulation, showing that positive crosstalk between Hh and NF-κB pathways is dependent upon KRAS mutation in PDAC.